PELATIHAN ANALISIS DATA KUANTITATIF DENGAN SOFTWARE SPSS SEBAGAI PENINGKATAN KETERAMPILAN OLAH DATA MAHASISWA UIN PALOPO - Erwin; Fasiha; Muh. Irshan Sachrir; Andi Nur Wahyuningsih; Hafid Sumarwadji (LPPM ITB AAS Indonesia Surakarta, 2025)
This community service program aims to improve the understanding and skills of quantitative data analysis at UIN Palopo students through quantitative data analysis training using SPSS software. The community service method used is participatory action, a method that places the community, especially students, in an empowerment program to solve the problems they face. This community service program is conducted in three stages: 1) the planning stage, which includes determining the community service target, determining the training topic, and determining the materials and tools used during the service. The second stage, implementation, includes SPSS application installation, an introduction to the application, in-depth material delivery, hands-on practice using SPSS, data processing and interpretation, and discussion sessions. The third stage, evaluation and monitoring, includes material evaluation, discussion sessions, and mentoring outside of the training. With an interactive and enjoyable approach, students master the theory and practice of using SPSS. This demonstrates that with ongoing training programs, students' data processing and analysis skills can develop rapidly, especially in applying SPSS for research and future careers.